Clinical, magnetic resonance imaging, surgical features and comparison of surgically treated intervertebral disc extrusion in French bulldogs - Albertini, Guillaume Marc; Stabile, Fabio; Marsh, Oliver; Uriarte, Ane (Frontiers in Veterinary Science, 2023)
Intervertebral disc (IVD) extrusion (IVDE) is the most reported neurological condition in French bulldogs (FBD). The aim of this study was to retrospectively evaluate neurological grade, magnetic resonance imaging (MRI), surgical findings and short-term recovery in surgically treated FBD diagnosed with IVDE referred to a single institution between January2020 and March2022 and to compare cervical and thoracolumbar IVDE. Data was gathered from medical records and analysed via Fischer's Exact-Test and Kruskal Wallis-tests. Statistical significance was assumed when p<0.05.Thirty-nine FBD were diagnosed with IVDE. Cervical IVDE (C-IVDE) was diagnosed in 11/39 cases; the C3-C4IVD space was the most commonly affected site (5/11). Thoracolumbar IVDE (TL-IVDE) was diagnosed in 28 cases; the L3-L4IVD space was the most commonly affected site (7/28). At admission, C-IVDE was significantly associated with less severe neurological grade (grade 1-2) compared to TL-IVDE (grade 2-5)(p<0.001). The extruded IVD material (EIVDM) was hypointense in T2w images in 11/11C-IVDE vs 2/28TL-IVDE, and hypointense in T1w images in 10/11C-IVDE vs 1/28TL-IVDE. The EIVDM was hyperintense in T2w images in 0/11C-IVDE vs 26/28TL-IVDE and iso-to-hypointense in T1w images in 1/11C-IVDE vs 27/28TL-IVDE (p<0,001). The EIVDM extended over >2IVD spaces in 0/11C-IVDE vs 19/28TL-IVDE (p<0,001). 10/11C-IVDE underwent single ventral slot, 1/11C-IVDE underwent unilateral cervical hemilaminectomy. All TL-IVDE underwent unilateral hemilaminectomy and 19/28TL-IVDE underwent unilateral hemilaminectomy over >2IVD spaces (p<0,001). Haemorrhagic EIVDM was noticed intraoperatively in 1/11C-IVDE vs 28/28TL-IVDE (p<0,001). Spinal cord compression was mild in 2/11C-IVDE and 3/28TL-IVDE; moderate in 9/11C-IVDE and 16/28TL-IVDE; severe in 0/11C-IVDE and 8/28TL-IVDE. There was no spinal cord compression in 1/28TL-IVDE with foraminal IVDE. There was no statistical difference between spinal cord compression and IVDE location (p=0.112). The mean time to improvement was 1.1 day in C-IVDE (range 1-2 days). 90.1% of C-IVDE improved within the first 24hours. The mean time to improvement was 2.1 days in TL-IVDE (range 1-4 days). All dogs that did not improve (5/39) were grade 5 TL-IVDEs at presentation.In FBD, TL-IVDE tended to cause higher grade of neurological dysfunction, tended to result in compression of neural structures over multiple IVD spaces and required more extensive surgical treatment than C-IVDE.